Law Enforcement Against Imported Used Clothing Trade Prohibition at Hartono Trade Center - Setiyani, Devy; Destyarini, Normalita; Prastyanti, Rina Arum (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The imported used clothing trade was found in Sukoharjo and has penetrated into modern markets such as the Hartono Trade Center (HTC). The import and trading activities of used clothing are prohibited by law because Imported used clothes have the potential to carry diseases. The purpose of this study was to determine law enforcement by the Department of Cooperatives, Small and Medium Enterprises and Trade in Sukoharjo Regency regarding the trading of imported used clothing in HTC and factors that affect the effectiveness of law enforcement. The research method used is empirical law with a sociological juridical approach while the data analysis technique is in the form of qualitative descriptive. The results obtained are law enforcement on the trade of imported used clothing carried out by the Office of Cooperatives, Small and Medium Enterprises and Trade of Sukoharjo Regency is not running optimally because monitoring and providing outreach activities related to imported used clothing and its dangers have never been carried out. Factor that affect the effectiveness of law enforcement on imported used clothing are internal factors, namely limited human resources and external factors, namely the legal awareness of traders and consumers who are still lacking in complying with laws and regulations.